TELA’AH ASAS ASAS PENDIDIKAN AKHLAQ ISLAM MENURUT MIQDAD YALJIN - Wimbadi, Ardan; Robiqoh, Ilma Umi (Universitas Islam Lamongan, 2024)
Declining student morals is a problem in modern education. Miqdad Yaljin, in his book